NAFKAH ISTRI DALAM PERSPEKTIF KESETARAAN GENDER: ANALISIS KRITIS DENGAN PENDEKATAN MAQASHID AL-SYARIAH - Ferdiansyah, Muhammad Ichsan; Wicaksono, Triadi; Lismawati, Lismawati (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study aims to analyze the concept of wife maintenance from the perspective of gender equality using  the maqashid sharia approach  by examining the gap between the normative construction of classical fiqh. This research method uses a qualitative approach based on library research with a focus on classical and contemporary fiqh texts, the Qur'an, hadith, and academic literature related to wife's maintenance, sharia maqashid, and gender equality. The research population included the entire Islamic legal literature on alimony with purposive sampling samples on relevant works. The research procedure includes data collection, classification based on the main theme, critical analysis with the framework of sharia maqashid, and synthesis of new concepts. Analysis techniques are in the form of content analysis and critical hermeneutics. The results of the study show that the understanding of classical fiqh is rigid and less responsive to modern socio-economic changes. Through the sharia maqashid approach, alimony can be understood more broadly, not only as a material obligation of the husband, but also as a collective responsibility that includes emotional, spiritual, and social aspects, according to the principles of justice and benefit. The conclusion of this study confirms that Islamic law is dynamic and adaptive, so the concept of alimony must be reinterpreted to be relevant to the modern context and support the principle of gender equality. The follow-up plan of the research is directed at empirical studies through field research and comparisons between Muslim countries.